2012
DOI: 10.1021/ja309141r
|View full text |Cite
|
Sign up to set email alerts
|

6,6-Dicyanopentafulvenes: Electronic Structure and Regioselectivity in [2 + 2] Cycloaddition–Retroelectrocyclization Reactions

Abstract: We present an investigation of the electronic properties and reactivity behavior of electron-accepting 6,6-dicyanopentafulvenes (DCFs). The electron paramagnetic resonance (EPR) spectra of the radical anion of a tetrakis(silylalkynyl) DCF, generated by Na metal reduction, show delocalization of both the charge and unpaired electron to the nitrogens of the cyano moieties and also, notably, to the silicon atoms of the four alkynyl moieties. By contrast, in the radical anion of the previously reported tetraphenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 42 publications
2
72
0
2
Order By: Relevance
“…2, 121.3, 123.6, 127.2, 127.7, 127.9, 128.1, 128.7, 129.7, 131.4, 133.2, 134.67, 134.69, 137.2, 137.9, 139.0, 141.0, 143.7, 148. 4, 122.2, 126.3, 127.2, 127.60, 127.65, 127.8, 128.1, 129.8, 131.4, 131.8, 133.7, 134.3, 135.0, 136.8, 138.9, 143.6, 143.8, 152. (dd, J = 1.6, 4.0 Hz, 1H); 13 C NMR (100 MHz, CDCl 3 ) δ 120. 9, 121.8, 122.9, 126.3, 126.7, 127.0, 127.4, 127.7, 127.9, 128.0, 128.4, 129.9, 131.5, 133.3, 134.4, 134.7, 134.9, 135.9, 138.3, 139.5, 140.2, 144.7, 150.9 2, 125.7, 126.9, 127.6, 129.2, 129.7, 130.1, 133.0, 137.4, 140.4, 143.5, 166 1, 126.5, 127.5 (overlapped), 127.6, 127.9, 128.7, 129.4, 129.7, 129.9, 135.75, 135.77, 137.5, 141.3; HRMS m/z Calcd for C 18 2, 123.5, 125.1, 126.0, 126.4, 126.9, 127.3, 127.5, 129.3, 129.4, 129.7, 129.9, 134.8, 135.6, 135.9, 137.4, 141.4; HRMS m/z Calcd for C 19 Hz, 1H); 13 C NMR (100 MHz, CDCl 3 ) δ 31. 3, 34.6, 123.6, 125.1, 125.6, 126.1, 126.3, 127.2, 127.4, 127.5, 129.4, 129.5, 129.9, 134.8, 135.6, 136.0, 141.4, 150.7 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 29 = 1.6, 5.…”
Section: Methodsmentioning
confidence: 99%
“…2, 121.3, 123.6, 127.2, 127.7, 127.9, 128.1, 128.7, 129.7, 131.4, 133.2, 134.67, 134.69, 137.2, 137.9, 139.0, 141.0, 143.7, 148. 4, 122.2, 126.3, 127.2, 127.60, 127.65, 127.8, 128.1, 129.8, 131.4, 131.8, 133.7, 134.3, 135.0, 136.8, 138.9, 143.6, 143.8, 152. (dd, J = 1.6, 4.0 Hz, 1H); 13 C NMR (100 MHz, CDCl 3 ) δ 120. 9, 121.8, 122.9, 126.3, 126.7, 127.0, 127.4, 127.7, 127.9, 128.0, 128.4, 129.9, 131.5, 133.3, 134.4, 134.7, 134.9, 135.9, 138.3, 139.5, 140.2, 144.7, 150.9 2, 125.7, 126.9, 127.6, 129.2, 129.7, 130.1, 133.0, 137.4, 140.4, 143.5, 166 1, 126.5, 127.5 (overlapped), 127.6, 127.9, 128.7, 129.4, 129.7, 129.9, 135.75, 135.77, 137.5, 141.3; HRMS m/z Calcd for C 18 2, 123.5, 125.1, 126.0, 126.4, 126.9, 127.3, 127.5, 129.3, 129.4, 129.7, 129.9, 134.8, 135.6, 135.9, 137.4, 141.4; HRMS m/z Calcd for C 19 Hz, 1H); 13 C NMR (100 MHz, CDCl 3 ) δ 31. 3, 34.6, 123.6, 125.1, 125.6, 126.1, 126.3, 127.2, 127.4, 127.5, 129.4, 129.5, 129.9, 134.8, 135.6, 136.0, 141.4, 150.7 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 29 = 1.6, 5.…”
Section: Methodsmentioning
confidence: 99%
“…[38] Sequential [2+ +2] CA-RE Reaction of 1-Azulenylbutadiynes with TCNE and TTF In 1991, Hopf et al reported the formal [2+ +2] CA-RE reaction of tetrathiafulvalene (TTF) with electron-deficient alkynes with dicyanoethylene substituents in the formation of 1,2-bis(1,3-dithiol-2-ylidene)ethane derivatives with donor-acceptor structures. [42] In regard to the electrochemical analysis, TCBD-TTF adduct 13 showedao ne-stage oxidation wave (+ 0.57 V) in CV owing Table 2. [40] Inspired by this research, we examined the reactiono fb utadiyne derivatives possessing terminal 1-azulenyl groups.…”
Section: Compoundmentioning
confidence: 99%
“…Recently first metallocene‐pentafulvene type complexes are synthesized and characterized . Although these studies demonstrate fulvene as an excellent functional molecule, the possibility of fulvene chemistry is not yet fully unravelled …”
Section: Introductionmentioning
confidence: 99%